Comparative Performance Analysis of Optimized Performance Round Robin Scheduling Algorithm(OPRR) with AN Based Round Robin Scheduling Algorithm using Dynamic Time Quantum in Real Time System with Arrival Time - Banerjee, Pallab; Kumari, Anita; Jha, Puja (International Journal of Computer Sciences and Engineering, 2015)
Round Robin is the most oldest and widely used scheduling algorithm but it has certain limitation because of static time quantum. Time quantum must be large so that context switching becomes reduces and it also effect the response time .So, in this paper we proposed a new algorithm called Optimized Performance Round Robin(OPRR) in which we focused on dynamic time quantum which give result as a very less context switching as well as average waiting time and average turnaround time. It also reduces the overhead of the CPU by adjusting the time quantum according to the highest burst time of the processes in the ready queue.